(untitled) (Global Journal of Science Frontier Research, 2012)
This study analyzed the effects of adoption of improved maize seed on household food security in Gwoza Local Government Area of Borno State. The study utilized primary data collected through questionnaire administered to 180 respondents selected through multi-stage sampling procedure. Data were analyzed using descriptive statistics (frequencies and percentages) and inferential statistical tools (the Probit model). The results revealed a preponderance of economically active respondents as the majority (73.33%) were between the ages of 26 and 55 years with most (87.78%) being male. While majority of the respondents (64%) had formal education, 36.67% of the respondents had no formal education. Majority of the respondents operate at small-scale (≤ 2ha). Analyses of determinants of adoption revealed that education and extension contact significantly influenced the likelihood of the adoption of improved maize seed (ρ ≤ .01). Access to credit also influenced the adoption of improved maize seed. The study also found that adoption of improved maize varieties reduced the incidence, depth and severity of food insecurity among farming households in the study area.